Analisis Yuridis Terhadap Dugaan Korupsi Impor Minyak Mentah Oleh Eksekutif PT Pertamina Patra Niaga - Kalvisanda, Shavinra Rosmiftafany; Wahyudi, Wahyudi (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
The case of alleged corruption in crude oil import activities involving PT Pertamina Patra Niaga has raised public concern because it has a major impact on the national economy and the level of public trust in state institutions. This research aims to evaluate the legal regulations that govern corruption crimes and examine the potential involvement of company executives in unlawful practices. The approach used is normative juridical, with secondary data sources in the form of legal literature, laws and regulations, and the results of interviews with experts in the legal field. The analysis was carried out qualitatively to understand the relationship between the legal framework and the reality of implementation in the field. The results of the study show that although anti-corruption regulations are available, their implementation is still weak and opens up opportunities for corruption in strategic sectors such as energy. This condition requires a comprehensive overhaul of the procurement, supervision, and law enforcement system. This research is expected to serve as a reference for policymakers in designing more effective corruption prevention strategies, emphasizing the importance of transparency, accountability, and the active participation of all stakeholders in the supervision of the energy sector.